2020
DOI: 10.1055/s-0040-1712157
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunity for Coronavirus Disease 2019: A Commentary on Therapeutic Aspects Including Convalescent Plasma

Abstract: In the ongoing pandemic of coronavirus disease 2019 (COVID-19), the novel virus SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) is infecting a naïve population. The innate immunity of the infected patient is unable to mount an effective defense, resulting in a severe illness with substantial morbidity and mortality. As most treatment modalities including antivirals and anti-inflammatory agents are mostly ineffective, an immunological approach is needed. The mechanism of innate immunity to this vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
(89 reference statements)
0
8
0
1
Order By: Relevance
“…In addition, a study recommended the collection of plasma at least 14 to 28 days post-resolution of clinical symptoms associated with COVID-19 [39]. Moreover, on the basis of previous experiences from SARS-CoV, a neutralizing antibody titer greater than 1:40 is recommended for SARS-CoV-2 [39,40]. Further studies may be required to evaluate the therapeutic potential of the convalescent plasma.…”
Section: Article Highlightsmentioning
confidence: 99%
“…In addition, a study recommended the collection of plasma at least 14 to 28 days post-resolution of clinical symptoms associated with COVID-19 [39]. Moreover, on the basis of previous experiences from SARS-CoV, a neutralizing antibody titer greater than 1:40 is recommended for SARS-CoV-2 [39,40]. Further studies may be required to evaluate the therapeutic potential of the convalescent plasma.…”
Section: Article Highlightsmentioning
confidence: 99%
“…The latter study highpoints a challenge in using convalescent sera, specifically that some who improve from the viral disease may not have high titers of neutralizing antibody. Dependable with this point, an analysis of 99 samples of convalescent sera from patients with SARS indicated that 87 had neutralizing antibody, with a geometric mean titer of 1: 61 33,34 . This recommends that antibody regressions with time or that some patients make high titer responses.…”
Section: Fig 1: Schematic Representation Of the Use Of Plasma Therapmentioning
confidence: 98%
“…►Table 3 lists the top 20 downloaded "Open Access" articles from STH (2019 and 2020 inclusive), as eligible for the "Open Access" award. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] ►Table 4 lists the top 25 downloaded non-open access articles from STH (2019 and 2020 inclusive), as otherwise eligible for the "'General Category" award. I will note that although I was a coauthor of one of the awardwinning articles, my relative contribution was minor in comparison to the lead author, and I will of course decline to receive any of the award prize.…”
Section: "Most Popular" Article Awardsmentioning
confidence: 99%